Identification of CDC20 as a Novel Biomarker in Diagnosis and Treatment of Wilms Tumor - Shi, Qinlin; Tang, Bo; Li, Yanping; Li, Yonglin; Lin, Tao; He, Dawei; Wei, Guanghui (Frontiers in Pediatrics, 2021)
Objective: Wilms’ tumor(WT) is a common malignant solid tumor in children. Many tumor biomarkers have been reported, however, there are poorly targetable molecular have been defined in WT. This study aim to identified the oncogene in WT and explored the potential mechanisms. Method: Differentially expressed genes(DEGs) in three independent RNA-seq datasets which were downloaded from The Cancer Genome Atlas (TCGA) data portal and the Gene Expression Omnibus (GEO) database (GSE66405 and GSE73209). The common DEGs were subjected to gene ontology (GO) enrichment analysis, protein-protein interaction (PPI) network analysis, gene enrichment analysis (GSEA). The protein expression level of hub-gene were analyzed by Immunohistochemical (IHC) and Western blotting (WB) in 60 WT sample. The univariate Kaplan-Meier analysis for overall survival was performed and the Log-Rank was utilized to test. A small interfering RNA (siRNA) targeting CDC20 was transfected into G401 and SK-NEP-1 cell lines. The Cell Counting Kit-8 (CCK-8) assay and Wound healing assay were used to observe the changes in cell proliferation and migration after transfection. Flow cytometry was used to detect the effect on the cell cycle. Western blot was conducted to study the changes of related functional proteins. Result: We identified commonly 44 up-regulation and 272 down-regulation DGEs in three independent RNA-seq datasets. Gene and pathway enrichment analyses of the regulatory networks involving hub genes suggested that cell cycle change are crucial in WT. The top 15 highly connected genes were found by protein-protein interaction (PPI) network analysis. Furthermore, we demonstrated that one candidate biomarker, Cell cycle 20(CDC20), for the diagnosis of WT was detected, and its high expression predicted poor prognosis of WT patients. Moreover, the AUC value obtained by ROC curve analysis from paired WT samples was 0.9181. Finally, we found that the suppression of CDC20 inhibited proliferation, migration and resulted in G2/M phase arrest in WT cells. The mechanism may be involved in increasing the protein level of Securin, Cyclin B1 and Cyclin A. Conclusion: Our results suggest that CDC20 could serve as a candidate diagnostic and prognostic biomarker for WT and suppression of CDC20 may be a potential approach to preventing and treating WT.